2008
DOI: 10.1111/j.1525-1470.2008.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive Juvenile Xanthogranuloma Associated with Relapsing Acute Lymphoblastic Leukemia

Abstract: Juvenile xanthogranuloma is a benign, self-healing disorder with characteristic lesions mainly involving the skin. Although most patients with juvenile xanthogranuloma have only cutaneous symptoms, recent articles have documented extracutaneous manifestations: systemic involvement of many organs has been reported and there is a known association between juvenile xanthogranuloma and childhood leukemia, most commonly juvenile chronic myelogenous leukemia. This case provides further corroboration, that in rare in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…According to some authors, the association is much higher in the presence of NF1 [32], but others have disputed the strength of this association [33]. Aparicio and colleagues [34] described a child with B-cell ALL in relapse who developed cutaneous JXG over much of the body. No NF1 features were present.…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, the association is much higher in the presence of NF1 [32], but others have disputed the strength of this association [33]. Aparicio and colleagues [34] described a child with B-cell ALL in relapse who developed cutaneous JXG over much of the body. No NF1 features were present.…”
Section: Discussionmentioning
confidence: 99%
“…The excess gamma globulins seen in leukaemia have been implicated in the stimulation of histiocytic proliferation and JXG formation. 11 The triple association of JXG, NF-1 and juvenile chronic myelogenous leukaemia (JCML) remains debatable. 1 One study reported a 20 to 32-fold increased risk of developing JCML in children with concomitant NF and JXG in comparison to NF-1 alone.…”
Section: Discussionmentioning
confidence: 99%
“…In BCH, the lesions have a roughly symmetrical distribution, mainly in the cephalocaudal progression; lesions do not appear in the palmar and plantar regions , and nose and scalp lesions are not common, as our cases showed. In disseminated JXG, asymmetrically distributed, scattered lesions appear over the entire body, including the palmar and plantar regions, and with typical nose and scalp involvement . Moreover, extracutaneous involvement, particularly eye manifestations, can be seen in JXG .…”
Section: Discussionmentioning
confidence: 99%